SOVIET COUNTER-INSURGENCY - Potgieter, T.D. (Scientia Militaria - South African Journal of Military Studies, 2012)
During the fifties and the sixties of this century counter insurgency was largely in Western hands. The eighties, however, seem to be the age of Soviet counter insurgency. After the Second World War several Western countries conducted counter insurgency campaigns in countries like Indo-China, Greece, Malaya, etc. Contemporary insurgency, on the other hand, seems to be aimed at communist governments in countries that have recently gained their independence. If one regards the fifties and sixties as a period of rising expectations in the Third World, the eighties could be called the age of unfulfilled expectations, because most modern insurgencies take place in countries that have recently become Marxist. Counter-insurgency is the action taken by (on behalf of) a constituted government against a group or groups waging a revolutionary war or conducting a localized armed rebellion (insurgency) against it, and is aimed at destroying such groups. Thus, counter-insurgency is of a counter-revolutionary nature.